Improve Online Purchasing Decisions Through Lifestyle, Risk Perception, and Consumer Trust in Shopee International Indonesia - Retno Wulandari; Muinah Fadhilah; Agus Dwi Cahya (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the influence of lifestyle, risk perception, and consumer trust on online purchase decisions at Shopee International Indonesia. The rapid development of internet technology and e-commerce has transformed consumer behavior, making it essential to understand the factors driving online purchasing decisions. This research aims to determine the influence of lifestyle, risk perception, and consumer confidence on online purchase decisions at Shopee International Indonesia. The research method employed is quantitative descriptive, with the sample consisting of customers who have purchased products through the Shopee online shop. The sampling technique used is purposive sampling, with a total of 100 questionnaires processed. Data were analyzed using SPSS version 25. The results show that the lifestyle variable has a positive and significant effect on online purchase decisions at Shopee International Indonesia. The risk perception variable has a negative and significant effect on online purchase decisions at Shopee International Indonesia. The consumer trust variable has a positive and significant effect on online purchase decisions at Shopee International Indonesia. Simultaneously, lifestyle, risk perception, and trust variables have a positive and significant effect on online purchase decisions at Shopee International Indonesia, with a contribution of 90.40%.